The impact of SGLT2 inhibitors on cardiac remodeling after myocardial infarction: an updated meta-analysis of randomized controlled trials - Xu, Ma Li; Wang, Hui; Ouyang, Dan; Qi, Hang; Li, Xin Hui (Frontiers in Pharmacology, 2025)
BackgroundRecent studies show that sodium-glucose linked transporter 2 inhibitors (SGLT2is) reduce blood glucose and provide cardiovascular benefits, decreasing acute myocardial ischemia/reperfusion injury in patients with acute myocardial infarction (AMI).ObjectiveThis meta-analysis aims to thoroughly assess the clinical effectiveness of SGLT2is in the treatment of AMI.MethodsRandomized controlled trials (RCTs) evaluating the efficacy of SGLT2is in combination with guideline-directed medical therapy (GDMT) for AMI were retrieved from major databases: PubMed, Cochrane Library, Embase, Medline, and Web of Science. At the same time, clinical trial registries (ClinicalTrials.gov and the WHO International Clinical Trials Registry Platform) were searched, covering all published literature up to May 2025. Using the Cochrane Collaboration for assessing the risk of bias, two independent reviewers preliminarily screened and assessed the studies according to the preset inclusion criteria. Meta-analysis was conducted using RevMan 5.4 software, and StataMP 16.0 was used to evaluate publication bias. The quality of evidence was graded according to recommended procedures for assessing and evaluating the evidence.ResultsFive RCTs with a total of 881 patients were included in this analysis. According to a meta-analysis, SGLT2is and GDMT significantly reduced NT-proBNP (RR = −89.82, 95% CI -96.28 to −83.35; p < 0.00001) and enhanced the 12-week left ventricular ejection fraction (LVEF) (RR = 6.32, 95% CI -4.95 to 17.60; p < 0.00001). Evaluation of additional cardiac structural and functional characteristics showed that the SGLT2i + GDMT group showed significantly reduced left atrial volume (LAV) (RR = −3.86, 95% CI -6.33 to −1.38; p = 0.002) and left atrial volume index (LAVI) (RR = −1.67, 95% CI -3.13 to −0.20; p = 0.03) when compared to the control group. There were decreases in LVESVI, LVEDVI, LVEDD, LVESD, LVESV, and LVEDV. Furthermore, subgroup analyses based on the LVEF at admission and the site of the infarct in AMI patients were carried out. Treatment with SGLT2i + GDMT led to a significantly higher improvement in the LVEF ≤40% group than in the LVEF >40% group (MD = 5.20, 95% CI 2.74 to 7.66; p < 0.0001). The cardiotonic troponin I (cTnI) levels in the LVEF >40% group showed a declining trend starting at 8 h post-onset and a notable improvement at 40 h post-onset. Significant improvement in cTnI levels was observed in the LVEF ≤40% group after 56 h post-onset (MD = −8.40, 95% CI −13.74 to −3.06; p = 0.002). Regarding the effect of the infarct location on LVEF recovery, patients with AMI treated with SGLT2i + GDMT demonstrated a significant improvement in LVEF, regardless of whether the myocardial infarction was in the anterior wall (MD = 4.20, 95% CI 0.88 to 7.52; p = 0.01) or the non-anterior wall (MD = 3.90, 95% CI 0.63 to 7.17; p = 0.02). As early as 16 h after commencement, both groups’ cTnI levels showed a declining trend. By 24 h after the onset, non-anterior myocardial infarction patients showed a substantial improvement in cTnI levels (MD = −1.70, 95% CI −11.92 to −2.28; p = 0.004). However, ST-segment resolution showed no significant differences between the two groups. The SGLT2i + GDMT group’s incidence rate for the primary endpoint major adverse cardiovascular events (MACEs) was nearly identical to that of the control group. Recurrent myocardial infarction (RR = 0.64, 95% CI 0.16–2.55; p = 0.53), stroke (RR = 2.71, 95% CI 0.11–68.25; p = 0.54), and cardiovascular disease-related death (RR = 1.47, 95% CI 0.29–7.56; p = 0.64) did not differ significantly from one another. The incidence of MACEs in the experimental group was essentially comparable to that in the control group. For other primary endpoints, the incidence of re-admission for heart failure showed a downward trend in the experimental group compared with the control group. Furthermore, although no significant hepatic or renal dysfunction was reported in the studies, meta-analysis indicated that SGLT2i combined with GDMT increased the incidence of drug-related adverse events, which primarily manifested as higher rates of genitourinary infections and acute kidney injury (RR = 1.88, 95% CI 1.03–3.42; p = 0.04).ConclusionAvailable data suggest that SGLT2i intervention may ameliorate detrimental early ventricular remodeling in individuals who have had an AMI, improve cardiac function, and aid in the recovery of cardiac function and structure.